Xenobiotic- and Serum-Free Culture of Oral Mucosal Epithelial Cells on Contact Lenses. (2nd January 2016) - Björkblom, Benny; Eidet, Jon R.; Utheim, Tor P.; Ulltveit-Moe, Harald F.; Raeder, Sten
Abstract: Purpose/aim : Cultured autologous oral mucosal epithelial cells (OMECs) have proven useful in the treatment of ocular surface disorders. This study is the first to investigate the potential of expanding OMEC in a xenobiotic- and serum-free medium using therapeutic contact lenses (CLs) as a substrate and carrier. Materials and methods : Porcine OMEC were seeded on laminin-coated lotrafilcon A therapeutic CLs with the density of 8 × 10 4  cells/lens and cultured in a defined serum and xenobiotic-free medium. Confocal immunofluorescence microscopy was used to analyze the following: (1) cellular morphology by using rhodamine-phalloidin staining of F-actin, (2) phenotype by applying antibodies against the progenitor cell marker p63 and the putative stem cell marker ABCG2 and (3) cell viability by using propidium iodide and Hoechst 33342 dual staining. Results : Porcine OMEC attached well to the CLs, and cell-to-cell contacts were evident. After three days in culture, the OMEC displayed a confluent monolayer with uniform cobblestone morphology, whereas stratified cultures with 2–3 layers were formed after six days. No significant difference in expression of p63 was observed after three-day culture (79.4 ± 14.8%) compared with six-day culture (60.3 ± 18.9%). ABCG2 expression in the basal cell layer was 6.3 ± 1.0% and 4.8 ± 1.8% after three- and six-day culture, respectively. The basal layer viability of cultured OMECs was 99.3 ± 0.2% and 82.8 ± 1.1% after three and six days culture, respectively. Conclusions : The use of therapeutic CLs has potential as a substrate and carrier for OMEC cultured in a xenobiotic- and serum-free culture system.